Evaluation of Treatment of Tinea Corporis and Tinea Cruris with Oral Terbinafine Using Direct Microscopic Examination with Special Stains - Sudhir Singh1 , Adarshlata Singh2 , Pankaj Mulchandani3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Terbinafine is a fungicidal allylamine drug and was considered a drug of choice to treat dermatophyteinfection. However recently there wasan increase in the incidence of clinical failure and relapses withterbinafine.Aims and Objectives: This study was undertaken to assess the effectiveness and safety of oral terbinafine250 mg given in patients suffering from tinea cruris and tinea corporis for 6 weeks.Materials and Method: In a prospective, open-label randomized controlled comparative trial 40 patientssuffering from tinea cruris and tinea corporis were recruited. Only patients with tinea cruris and tineacorporis, confirmed through positive microscopy before the start of treatment were eligible for inclusionin the trial. The patients were distributed into two groups and randomly allocated into group A and groupB of 20 patients each. Both groups received the same treatment i.e., oral Terbinafine 250mg once daily for6 weeks. Patients of both groups were followed up at weeks 2, 4, 6 during treatment and at the end of 8weeks. Mycological control test for group A and group B patients were done by KOH mount at baselineand each visit. Patients of group B underwent mycological control testing in the form of KOH mount withthe concurrent use of DMSO and CSB at baseline and each visit. By the end of treatment clinical andmycological cure were evaluated.Results: In group A (mycological testing with only KOH was done), fungal elements were detected in100%, 40%, 20%, 0% and 0% of baseline patients, 2 weeks, 4 weeks, 6 weeks and 8 weeks respectively.In group B (mycological testing with KOH and DMSO+CSB was done), fungal elements were detected in100%, 75%, 50%, 10% and 15% of baseline patients, 2 weeks, 4 weeks, 6 weeks and 8 weeks respectively.Even after 2 weeks of completion of oral terbinafine 250 mg for 6 weeks,the clinical cure was not seen in40% and 35% patients in groupA and group B.Conclusion: Although mycological cure was achieved in more than 90% of patients in group A and group Bafter 8 weeks clinical cure was achieved in only 60% and 65 % patients in group A and group B respectively.Implying that we need to continue oral terbinafine for a longer period to achieve mycological as well as aclinical cure.